Reinforcement Sensitivity Theory, approach-affect and avoidance-affect. Issue 4 (19th May 2021) - Warr, Peter B.; Sánchez-Cardona, Israel; Taneva, Stanimira K.; Vera, Maria; Bindl, Uta K.; Cifre, Eva
ABSTRACT: This paper brings together Reinforcement Sensitivity Theory and other perspectives on wellbeing to test predictions about dimensions of affect which are linked to approach motivation or avoidance motivation. Valence and activation are jointly conceptualised as either approach-affect or avoidance-affect through the diagonal axes of an affective circumplex. Across four studies in three different countries, predictions about Reinforcement Sensitivity Theory's Behavioural Activation System, Behavioural Inhibition System and Fight-Flight-Freeze System are found to be supported. Correlations with external variables are shown to depend on a wellbeing measure's emphasis on approach or avoidance, such that affect and external features which both emphasise motivation to approach or to avoid yield substantially larger intercorrelations than do non-concordant pairs. In addition, joining valence with activation is shown to yield correlational benefits as predicted. Implications of our perspective and operationalisation are reviewed, and specific research recommendations are made.